Development of Student Worksheet with Guided Discovery Oriented to Train HOTS on Thermochemistry Matter - Malichah, Siti; Yonata, Bertha (JCER (Journal of Chemistry Education Research), 2023)
This research purpose to describe the feasibility of student worksheet with guided discovery oriented to train HOTS on thermochemistry matter. Research metodology that used based on Sugiyono (2016) which consist of 10 stages, but this research is limited to product trial stages. The result shows that the student worksheet is feasible on the validity aspect which viewed from content validity and construct validity. The content validity get percentage of 85.76% for student worksheet 1 and 85.91% for student worksheet 2. The construct validity obtained percentage of 87.16% for student worksheet 1 and 2. Practicality aspect is viewed from student responses that get percentage in range 75-100% and observation of students activities shows that overall relevant activities are greater than not relevant activities. Effectiveness aspect is viewed from the students HOTS test result that get gain score in range 0.58-0.96 and knowledge domain test result with >80% of classical completeness.